Effect of dietary carbohydrate on the growth performance, immune response, hepatic antioxidant abilities and heat shock protein 70 expression of Wuchang bream, Megalobrama amblycephala. (13th July 2013) - Zhou, C.; Liu, B.; Ge, X.; Xie, J.; Xu, P.
Summary To investigate the effects of different carbohydrate (CHO) levels in the diet of Wuchang bream Megalobrama amblycephala, the fish were randomly divided into six treatment groups. Five groups were fed 19, 25, 31, 38 and 47% CHO, respectively, for 8 weeks, and a control group was fed a diet with no CHO. Growth performance and feed utilization were significantly (P < 0.05) affected by the dietary carbohydrate level. Maximum weight gain and specific growth rate occurred at the 31% dietary carbohydrate level. Compared to the control, the 31% CHO group had a significantly increased serum total protein content, respiratory burst activity of leucocytes, serum complement 3 (C3) levels, serum lysozyme activity, serum alkaline phosphatase (AKP) activity and hepatic total antioxidative capacity (T‐AOC), as well as a decrease in serum glutamic‐oxaloacetic transaminase (GOT) activity. Compared to the control, the 47% CHO group had significantly increased serum GOT activity, and a tendency toward an increase in serum cortisol content and a decrease in serum lysozyme activity, hepatic superoxide dismutase (SOD) activity and T‐AOC. The relative level of hepatic heat shock protein 70 (HSP70) mRNA in fish fed the 38% CHO diet was significantly higher than those of fish fed the 19, 25 and 31% CHO diets, respectively (P < 0.05). After challenge with Aeromonas hydrophila, fish fed the 47% CHO had the significantly lowest post‐challenge survival, and fish fed the 31% CHO had the significantly highest post‐challenge survival (P < 0.05). The results of this study suggest that ingestion of excessive dietary CHO can impact the non‐specific immune responses, decrease the hepatic antioxidant abilities, and thus affect the health status of M. amblycephala.